PELAKSANAAN PUTUSAN HAKIM TERHADAP PEMENUHAN NAFKAH ANAK PASCA PERCERAIAN (STUDI PENELITIAN DI MAHKAMAH SYAR’IYAH BIREUEN) - Khairani, Ridha; Aksa, Fauzah Nur; Afrizal, Teuku Yudi; maghfirah, fitri (Prodi Ilmu Hukum, Universitas Teuku Umar, 2024)
The judge's decision determines child custody after divorce. In some cases, the child's custody rights are given to the mother or father, and in implementation, there are parents who do not heed the results of the judge's decision, so that the plaintiff must carry out the execution by submitting the contents of the petition or withdrawing the point of claim such as the Syar'iyah Court Decision Number 594/ Pdt.G/2021/MS.Bir and Decision Number 97/Pdt.G/2023/MS.Bir. This research aims to find out and explain the analysis of the judge's decision regarding the fulfillment of child support based on the Syar'iyah Court Decision Number 594/Pdt.G/2021/MS.Bir and 97/Pdt.G/2023/MS.Bir and to find out the obstacles and the efforts taken in implementing the Shar'iyah Court Decision Number 594/Pdt.G/2021/MS.Bir and Decision Number 97/Pdt.G/2023/MS.Bir. This type of research is qualitative research with an Empirical Juridical approach, and the nature of the research is descriptive. Based on the results of the research, it is known that before determining the cost of child support rights, the judge first confirms the parties involved, then the judge will also analyze the ability of the party charged with child support due to divorce. There are no obstacles in implementing the Shar'iyah Court decision Number 594/Pdt.G/2021/MS.Bir and Decision Number 97/Pdt.G/2023/MS.Bir, and if the father does not fulfill his obligations as stated in the decision, then the father does not receive sanctions, because the court's obligations do not reach the stage of giving sanctions to the father, so the solution given is that the mother must apply for execution or submit a request for the contents of the decision. If this effort is also unsuccessful, then legal efforts can be taken that can protect children from irresponsible parental actions in Article 76 B and Article 77 B of Law Number 35 of 2014 concerning Child Protection.